2016
DOI: 10.4172/2157-7560.1000340
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Intensification of Bivalent Oral Poliovirus Vaccine Use Prior to its Coordinated Global Cessation

Abstract: Objective To examine the impact of different bivalent oral poliovirus vaccine (bOPV) supplemental immunization activity (SIA) strategies on population immunity to serotype 1 and 3 poliovirus transmission and circulating vaccine-derived poliovirus (cVDPV) risks before and after globally-coordinated cessation of serotype 1 and 3 oral poliovirus vaccine (OPV13 cessation). Methods We adapt mathematical models that previously informed vaccine choices ahead of the trivalent oral poliovirus vaccine to bOPV switch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Prior work suggested that the die-out behavior remains similar for all 3 poliovirus serotypes [ 21 ]. However, given different assumptions about the transmissibility and reversion rate of OPV1 and OPV3 compared to OPV2 ( Table 1 ), the population immunity and OPV coverage thresholds needed to prevent cVDPV1 and cVDPV3 outbreaks after OPV13 cessation differ somewhat compared to serotype 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work suggested that the die-out behavior remains similar for all 3 poliovirus serotypes [ 21 ]. However, given different assumptions about the transmissibility and reversion rate of OPV1 and OPV3 compared to OPV2 ( Table 1 ), the population immunity and OPV coverage thresholds needed to prevent cVDPV1 and cVDPV3 outbreaks after OPV13 cessation differ somewhat compared to serotype 2.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the assumptions used in the model shown in Table 1 imply that safe OPV1 cessation requires lower population immunity to transmission than OPV2 cessation, but higher routine immunization coverage (with bOPV) due to lower take rates and secondary immunity for OPV1 than for OPV2. For OPV3 cessation, both the minimum population immunity level and the minimum routine immunization coverage remain lower than for OPV1 or OPV2 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Nigeria historically exported WPV1 to numerous countries in Africa and elsewhere that did not maintain sufficient population immunity to poliovirus transmission [48], countries with poor RI coverage remain at risk. These countries need to continue to conduct preventive SIAs, using bOPV, to keep their population immunity to transmission high and prevent any importations of the circulating WPV1 from restarting transmission and causing new outbreaks within their borders [49]. The increased use of inactivated poliovirus vaccine (IPV), which results in a weaker immune response at the individual level and leads to relatively lower population immunity to transmission than OPV, will not play an important role in preventing cVDPVs in OPV-using countries prior to bOPV cessation [50], substantially accelerate eradication in polio-endemic countries [36][37][38], or represent a cost-effective option when used in addition to OPV in outbreak response [51].…”
Section: Resultsmentioning
confidence: 99%
“…Among countries and territories procuring bOPV through UNICEF, SIAs are the key demand driver, with routine immunization accounting for approximately 20% of UNICEF’s procurement of 1.2 billion doses in 2016. Similar to tOPV withdrawal, successful withdrawal of bOPV will depend on finding a balance between the scaling back of production by global and domestic manufacturers and ensuring sufficient availability of types 1 and 3 bulk and finished bOPV to meet routine immunization, outbreak response, and planned SIA demand through the date of OPV withdrawal [ 13 ]. Factors that can facilitate a favorable balance include advanced notification of the date of withdrawal to manufacturers and countries, inventories of countries’ OPV stocks, and accurate country and global quantification of demand for bOPV.…”
Section: Manufacturing and Distribution Of Bivalent Opvmentioning
confidence: 99%